Testing the Effectiveness of Azotobacter Bacteria and Organic Materials on the Growth, Production, Assembly of Plant N and Soil N Availability in Kailan Plants (Brassica Oleraceae) - Alki Satrio Plapito; Aisyah Aisyah; Paranita Asnur (Gontor AGROTECH Science Journal, 2021)
The attractiveness of organic agriculture, has high economic and social value, low production of organic kailan horticultural commodities causes market demand not to be fulfilled. Efforts that can be applied and applied to support the growth and development of kailan plants are the use of the Bacteria Azotobacter sp. This study aims to determine the effect of the inoculation of the Azotobacter sp. The administration of organic matter and the interaction between the inoculation of Azotobacter. sp and the provision of organic matter on the growth, production and uptake of plant N and soil N availability in kailan plants. The design used in this study was a 2-factor factorial Completely Randomized Design (CRD). The first factor was the isolation of Azotobacter sp consisting of 3 levels, namely, a dose of 0 ml, 10 ml and 20 ml. The second factor is the provision of organic material in the form of goat manure which consists of 2 levels, namely, without giving organic material and giving 100 gr of organic material. From the results of data analysis, it was found that the inoculation of bacteria had an Azotobacter sp effect on the growth and production and uptake of plant N in kailan plants, it could be seen in the parameters of plant height, number of leaves, stem diameter, leaf area, shoot wet weight, and plant N uptake. Organic matter affects the growth and production as well as plant N uptake and soil N availability in kailan plants, this can be seen in the parameters of plant height, number of leaves, stem diameter, leaf area, crown weight, shoot dry weight, plant N uptake and availability. N land. The interaction between Bacterial inoculation Azotobacter sp. and organic matter affects plant growth and production, including plant height, leaf area and plant N uptake.